Pengembangan bahan ajar materi geometri dimensi tiga dengan menggunakan pendekatan saintifik berbantuan geogebra - M Nasrulloh; Asep Ikin Sugandi (IKIP Siliwangi, 2023)
This study aims to examine the process of developing teaching materials, the feasibility of teaching materials, the effectiveness of teaching materials and the constraints found during the development of three-dimensional heometric teaching materials. The research method uses Research and Development (R&D) with test and non-test instruments. Data processing was carried out using Microsoft Excel 2019. The subjects in the study were divided into two parts, in the limited trial 10 class XII students who had studied three-dimensional geometry, the broad trial consisted of 20 class XII students who had not studied three-dimensional geometry material at SMK. The results showed that the process of developing teaching materials was in accordance with the Robert Maribe Branch stages, the feasibility of three-dimensional geometry teaching materials using a geogebra-assisted scientific approach to solving class XII SMK problems according to experts and practitioners obtained results in the